Protein kinase activity associated with the product of the yeast cell division cycle gene CDC28. - Reed, S I (1985)
Antibodies raised against the protein encoded by a lacZ-CDC28 in-frame fusion were shown to immunoprecipitate the CDC28 product from yeast cell lysates. The polypeptide p36CDC28 is a phosphoprotein of apparent Mr 36,000. Immune complexes prepared from yeast cell lysates by using anti-CDC28 antibody were found to possess a protein kinase activity, as determined by the transfer of label from [gamma-32P]ATP to a coprecipitated Mr 40,000 protein of unknown identity or function (p40). This activity was absent or thermolabile when extracts were prepared from several different cdc28 temperature-sensitive strains. The protein kinase activity was dependent on Zn2+ and transferred phosphate specifically to serine and threonine residues.